The characteristic of sago-based edible films incorporated with different antimicrobial essential oils: article / Nurul Amalina Shari and Fariza Hamidon - Shari, Nurul Amalina; Hamidon, Fariza (2017)
Sago films incorporated with essential oils (EOs) was produced to study their characteristics and antimicrobial effectiveness against Escherichia coli. The films were prepared by heating a mixture of sago starch and glycerol as plasticizer. Two concentration of glycerol were used, 0.6 and 1.0 mL with an incorporation of antimicrobial agent such as turmeric (TO) and lemongrass (LGO) EO to film mixture with different concentration (0.2%, to 0.5% v/v). Tensile testing machine was used to measure the tensile strength (TS) and elongation at break (EB) of the sago film. Other characterization including water vapor permeation (WVP), antimicrobial activity and color of the films. The sago film with 0.6 mL amount of glycerol for both EOs incorporated have slightly increased the tensile strength and elongation at break as concentration of EOs increased. WVP for 0.6 mL glycerol film with both EOs have increased compare to film with 1.0 mL glycerol which having the decreasing amount of WVP as the concentration of EO increased. Antimicrobial activity was test against Escherichia coli (E.coli). Result showed that sago film with LGO at 0.2%v/v has the lowest total colony count for both amount of glycerol added to films. Both films with 0.6 mL and 1.0 mL glycerol incorporated with LGO and turmeric have a significant yellow color compared to commercialize ziploc sandwich bag bought from supermarket.